A simulation study on factors affecting airwaves using factorial design - Abdulkarim, M. (2013)
In shallow water Sea Bed Logging (SBL) survey, air layer response from the Electro-Magnetic (EM) signals creates a disturbance known as the source-induced airwaves. The airwaves commonly denote the energy that propagates from the EM source via the atmosphere to the receiver on the seabed. As a result, the airwaves dominate the measured survey data, so that the sought-after signals from possible hydrocarbon layers in the subsurface can be totally masked. In this study, a 5x5 factorial design is used to analyze the effect of frequency, seawater conductivity, sediment conductivity, seawater depth and offset on the magnitude of airwaves. The result based on F-statistics, indicates that frequency has higher significant effect on the magnitude of the airwaves followed by the seawater depth, offset, seawater conductivity and sediment conductivity in that order. Â© 2013 Springer International Publishing.